2007
DOI: 10.2353/ajpath.2007.060850
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator Induces Pancreatic Cancer Cell Proliferation by a Non-Catalytic Mechanism That Requires Extracellular Signal-Regulated Kinase 1/2 Activation through Epidermal Growth Factor Receptor and Annexin A2

Abstract: Tissue plasminogen activator (tPA) is overexpressed in pancreatic ductal carcinoma and is involved in tumor progression. This effect is probably mediated through the activation of angiogenesis, cell invasion, and cell proliferation. Previous studies support the notion that the effects of tPA on cell invasion require its proteolytic activity. Here, we report the molecular mechanism responsible for the proliferative effects of tPA on pancreatic tumor cells. tPA activates the extracellular signal-regulated kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 63 publications
1
63
0
Order By: Relevance
“…We surprisingly found that small interfering RNA (siRNA) knockdown of LRP-1, the major cell membrane receptor of tPA mediating multiple cytokine actions of tPA in fibroblasts, 8,[12][13][14][15] had little effect on p65 phosphorylation in macrophages ( Figure 2B), suggesting that LRP-1 does not mediate the tPA-activated NF-kB pathway in macrophages. Instead, knockdown of the expression of annexin A2, another cell-surface receptor for tPA 21,22 that has the signaling potential, 22,24,25 abolished tPA-induced NF-kB activation in macrophages (Figure 2, C and D). Thus, it is clear that annexin A2 but not LRP-1 mediates tPA-activated NF-kB signaling cascade in macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We surprisingly found that small interfering RNA (siRNA) knockdown of LRP-1, the major cell membrane receptor of tPA mediating multiple cytokine actions of tPA in fibroblasts, 8,[12][13][14][15] had little effect on p65 phosphorylation in macrophages ( Figure 2B), suggesting that LRP-1 does not mediate the tPA-activated NF-kB pathway in macrophages. Instead, knockdown of the expression of annexin A2, another cell-surface receptor for tPA 21,22 that has the signaling potential, 22,24,25 abolished tPA-induced NF-kB activation in macrophages (Figure 2, C and D). Thus, it is clear that annexin A2 but not LRP-1 mediates tPA-activated NF-kB signaling cascade in macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…20 Annexin A2 has been identified as a major membrane receptor of tPA on endothelial, 21 microglia cells, 22 and other cancer cells, 23 and it is implicated in mediating certain signal transductions. 22,24,25 However, unlike the other well-known tPA receptor, LDL receptor-related protein 1 (LRP-1), annexin A2 is a membrane-associated protein, lacking transmembrane domain to which tPA can only dock. 20,23 It remains unknown how annexin A2 transactivates the intracellular signaling cascade initiated by the binding of extracellular tPA.…”
mentioning
confidence: 99%
“…However, we cannot rule out the possibility that the relationship between membranous expression of annexin 2 and S100A6 level is a consequence, rather than a cause, of the effect of S100A6 on motility. In addition, the interaction between annexin 2 and S100A6 may contribute to increased tPA activity, which could lead to a variety of effects, potentially including increased cell motility (Ortiz-Zapater et al, 2007;Sharma and Sharma, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The identified proteins included the known binding partners annexin 11 (Mizutani et al, 1992), annexin 2 (Zeng et al, 1993), and tropomyosin (Golitsina et al, 1996) as well as a candidate novel interactor lamin B1. As both S100A6 and annexin 2 are overexpressed in pancreatic cancer, with expression occurring early in the development of the cancer in both cases (Sitek et al, 2005;Vimalachandran et al, 2005;Esposito et al, 2006;Ortiz-Zapater et al, 2007), we focused our attention particularly on annexin 2.…”
Section: Identification Of S100a6-binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation